A Production systems study at the Manila Thermal Plant - Dimaculangan, Eric P.; Padilla, Ferdinand S.; Uy, Bryan C. (Diliman, Quezon City College of Engineering, 1995)
A production systems study at the Manila Thermal Plant (MNTP) was conducted. The said plant, situated on the Isla de Provisor on the Pasig River near Malacanang Palace, is one of the five thermal plants under the jurisdiction of the Metro Manila Regional Center (MMRC). MMRC controls, manages and maintains the main segment of the Luzon Grid of the National Power Corporation (NAPOCOR). The two units of the MNTP are currently underutilized, having a combined rated output of 169 MW, short of its 200 MW design capability. This underutilization, referred to as reduced capability in plant vocabulary, was traced primarily on the lowering of the operating pressure of the boilers. In turn, this was attributed to the deteriorating condition of the secondary superheater tubes (SSH). The tubes had to be replaced if the plant is to operate at higher capability. However, such items take one (1) year to procure from foreign suppliers. The order was made and an overhaul ( to replace the tubes) was scheduled. In the meantime, the plant remains underutilized. Purchase Requisitions for replacement items are made only when the inspections identify signs of deterioration. The policy is reactionary. This is the main problem in the plant. Having identified the problem, a Linear Programming model was developed to identify the optimal distribution of loads among the five thermal plants. Actual annual generated output was compared with the ideal output identified in the LP and the opportunity cost was computed as P57.4M annually. With the huge opportunity cost as basis, regular replacement of critical parts was recommended. Implementation of a Local Area Network (LAN) was also discussed and recommended.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Manila Thermal Plant; Chemical plants; Production engineering